Horizontal inequity in health care utilization in Japan - Chika Honda; Yasushi Ohkusa (Osaka University, Institute of Social and Economic Research (ISER), 2002)
International comparisons of horizontal inequity in health have recently become one of the most pertinent issues in health economics. Japan has not been included in these international comparisons. This omission is rectified in this paper, which focuses on Japan. Moreover, we consider its dynamics over six years from 1992 to 1998. The dynamics has never considered in this fields. In a rigorous international comparison, we cannot find any horizontal inequity in health in Japan and almost similar to Belgium.
Keywords: 330; Horizontal Inequity; Japan; International Comparisons; Concentration Index; Needs; Gesundheitswesen; Gesundheitsversorgung; Japan; Soziale Ungleichheit